Court of the Moon, Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
The 400-foot Tower of the Sun looms over the exquisitely lighted Court of the Moon at San Francisco's World's Fair, Treasure Island. Fluorescent tubes of colored lights produce the restful blue coloring and contrasting tints permeating this Court.